Enhancing reading comprehension through make a match with control board at SDN 112/II Purwo Bakti - Cut Dara Nadia Ladiski; Aprizan Aprizan; Elvima Nofrianni (Universitas Pendidikan Indonesia, 2025)
Reading comprehension is a fundamental skill essential for elementary school students; however, many still struggle to understand the content of texts. This condition was also identified at SDN 112/II Purwo Bakti, where most fourth-grade students had not yet achieved the minimum mastery criteria. This study aimed to enhance students’ reading comprehension skills through the application of the cooperative learning model,